LEADING THROUGH CHANGE CAN HAPPEN EFFECTIVELY ONLY IF A FULL UNDERSTANDING AND APPRECIATION OF ORGANIZATIONAL CULTURE IS PROGRESSIVELY DEVELOPED - Kyurova, Anita (Revista Inclusiones, 2021)
In today’s globalised world, leadership allows organizations to find the most effective and appropriate management activity. At the same time, leadership is crucial in contemporary times, allowing companies to adapt to changing environments. Leaders who focus their attention and knowledge on the organizational culture have the opportunity to effectively manage organizations. Knowing the organizational culture can contribute to the discovery and implementation of organizational change. Thus, it is crucial to explore the relationship between organizational culture and leadership and how they lead to competitive advantage and successful implementation of change within organizations. In this context, this research aims to explore the concept of leadership and organizational culture and how the full understanding and appreciation of the organizational culture can lead to effective organizational change.